Integrated vibration packing-sintering process for ITO rotary targets via slurry rheology and discrete element method simulations - Xiaokai Liu; Wenyu Zhang; Hetao Zhao; Benshuang Sun; Xina Liang; Bo Wei; Jiancun Ying; Huiyu Zhang; Yongge Zhao; Yongchun Shu; Yang Liu; Jilin He (Journal of Materials Research and Technology)
This study fabricates large-size rotary ITO targets using sand milling-slurry preparation, spray granulation, vibration packing, and atmospheric sintering. The effect of the rheological properties of ITO slurry on the particle morphology of the granulated powders was systematically investigated. The results show that spherical ITO granules can be successfully prepared when the slurry viscosity is 202.9 mPa s and the average particle size is 118 nm. Subsequently, Discrete element method (DEM) simulations and numerical analysis indicated that, with the increase in vibration frequency, the powder packing density initially increases and then decreases. Sintering experiments confirmed that the initial packing density influences the final sintering density. Through optimization of vibration frequency and sintering process, a large-size rotating ITO target with a density of 99.90 %, resistivity of 0.12 mΩ cm, average grain size of 5.33 μm, outer diameter of 156 mm, thickness of 13 mm, and height of 655 mm was successfully fabricated.